Aerobic fitness, maturation, and training experience in youth basketball - Carvalho, H. M.; Coelho e Silva, M. J.; Eisenmann, J. C.; Malina, R. M. (International Journal of Sports Physiology and Performance, 2013)
Relationships among chronological age (CA), maturation, training experience, and body dimensions with peak oxygen uptake (VO2max) were considered in male basketball players 14-16 y of age. Data for all players included maturity status estimated as percentage of predicted adult height attained at the time of the study (Khamis-Roche protocol), years of training, body dimensions, and VO2max (incremental maximal test on a treadmill). Proportional allometric models derived from stepwise regressions were used to incorporate either CA or maturity status and to incorporate years of formal training in basketball. Estimates for size exponents (95% CI) from the separate allometric models for VO2max were height 2.16 (1.23-3.09), body mass 0.65 (0.37-0.93), and fat-free mass 0.73 (0.46-1.02). Body dimensions explained 39% to 44% of variance. The independent variables in the proportional allometric models explained 47% to 60% of variance in VO2max. Estimated maturity status (11-16% of explained variance) and training experience (7-11% of explained variance) were significant predictors with either body mass or estimated fat-free mass (P = .01) but not with height. Biological maturity status and training experience in basketball had a significant contribution to VO2max via body mass and fat-free fat mass and also had an independent positive relation with aerobic performance. The results highlight the importance of considering variation associated with biological maturation in aerobic performance of late-adolescent boys.